INFLUENCE OF ISONIAZID ON THE METABOLISM OF RIFAMPICIN ON MT HEPATOCYTES - Fasich Fasich; Suharjono Suharjono; I Ketut Mandikin; Mulja Hadi Santosa (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2000)
Research on the influence of isoniazid on rifampicin metabolism using rat hepatocytes has been done. As the system metabolism, hepatocytes suspension was prepared by perfusion in the calcium binding media containing EDTA, citrate and glycine was used. In the experiment, combination of rifampicin and INH on various doses was incubated in those metabolism system at 30oC from 0 and up to 180 minutes duration. Then, analysis was done by thin layer chromathography and densitomeric method for each incubation intervals. Result calculated on the base of variation of rifampicin AUC-value beginning from 0 up to 180 minutes showed that isoniazid with concentration 5 µl, 10 µl, 15 µl, and 20 µl did not influence the metabolism of rifampicin (10 µl/ml) as showed by no significance changes of AUC value of rifampicin for Î± = 0.05.